(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Increased intracranial pressure (ICP) is a life-threatening condition that happens when there’s an imbalance between your brain tissue, cerebrospinal fluid and brain blood volume. It has several possible causes. Signs often include headache, vomiting and vision changes. The sooner you get treatment for ICP, the better.